Comparing Soybean Productivity, Soil Health, and Economic Viability Under No-Tillage and Conventional Tillage in the Lower Mississippi Delta - Saseendran S. Anapalli; Mubvumba Partson; Srinivasa R. Pinnamaneni; Krishna N. Reddy; Jonathan K. Corser (International Journal of Agronomy)
No-tillage (NT) management protects soil from wind and water erosion and improves soil health. Uncertainty in farm production under location-specific NT practices poses challenges to adopting it by the farming community. To address this challenge, a 4-year study (2019–2022) was conducted on farm-size plots (∼1.25 ha) focused on comparing soybean (Glycine max [L.] Merr.) yield and soil health benefits of an NT system with a conventional tillage (CT) system in silt loam soil. The NT and CT plots were under corn production over the previous 11 years. Compared to CT, in the 0–20 cm layer, soil bulk density (ρ), total nitrogen (TN), and soil organic carbon (C) increased, but field-saturated hydraulic conductivity (Kfs) decreased in the 10 cm below the soil surface under NT. Higher ρ was also noticed in the 10–30 cm soil. There were no significant differences between NT and CT in water stable aggregate stability for 0.25–0.5, 0.5–1.0, 1.0–2.0, and 2.0–4.0 mm aggregate classes. While the higher ρ and lower Kfs under NT can potentially restrict plant root expansion, the beneficial effects of C and TN appear to make up for those adverse effects, culminating in comparable seed yield returns. Over four years, soybean seed harvested from NT (5440 kg ha−1) was 1% less than CT (5480 kg ha−1). Therefore, adopting the NT system increases net returns by reducing tillage-associated expenses without compromising soybean yields in the Lower Mississippi Delta region, which can improve soil and water conservation.